2006
DOI: 10.1152/ajpgi.00338.2005
|View full text |Cite
|
Sign up to set email alerts
|

Differential effect of imipenem treatment on injury caused by cecal ligation and puncture in wild-type and NK cell-deficient β2-microgloblin knockout mice

Abstract: Our previous studies showed that beta(2)-microglobulin knockout mice treated with anti-asialoGM1 (beta2MKO/alphaAsGM1 mice) are resistant to injury caused by cecal ligation and puncture (CLP). However, CLP-induced injury is complex. Potential mechanisms of injury include systemic infection, cecal ischemia, and translocation of bacterial toxins such as endotoxin and superantigens. Currently, it is unclear which of these mechanisms of injury contributes to mortality in wild-type mice and whether beta2MKO/alphaAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…Several studies demonstrated that bacterial translocation is an important initiating mechanism for the induction of systemic inflammation and organ injury after CLP as removal of the cecal contents or treatment with powerful antibiotics reduce mortality and organ dysfunction (12,13). We showed in the present study that high bacterial counts were observed in blood and peritoneal cavity (Fig.…”
Section: Markers Of Organ Injury and Dysfunction Markers Of Systemsupporting
confidence: 63%
“…Several studies demonstrated that bacterial translocation is an important initiating mechanism for the induction of systemic inflammation and organ injury after CLP as removal of the cecal contents or treatment with powerful antibiotics reduce mortality and organ dysfunction (12,13). We showed in the present study that high bacterial counts were observed in blood and peritoneal cavity (Fig.…”
Section: Markers Of Organ Injury and Dysfunction Markers Of Systemsupporting
confidence: 63%
“…Our studies using ␤ 2 -microglobulin knockout mice show decreased systemic inflammation, less cardiovascular dysfunction, and improved survival after CLP, compared with wildtype controls (11)(12)(13). However, ␤ 2 -microglobulin knockout mice have multiple immunological defects in addition to NKT cell deficiency (14,15).…”
mentioning
confidence: 61%
“…In addition, the inclusion of antibiotics in these experimental animal models has varied tremendously with regard to the type of antibiotic, dose, route, and even dosing schedule. Some studies demonstrated improved outcomes (16,17,30,31) or a delay in mortality (32) after CLP in the presence of antibiotics, whereas other studies did not show an improved survival rate (33). Thus, the efficacy of antibiotic treatment in an experimental murine model remains unclear.…”
Section: Figmentioning
confidence: 99%
“…In the present study, we evaluated systematically the contribution of antibiotics in an acute model of sepsis induced by CLP. We used imipenem as the antibiotic of choice for its broad spectrum, covering most enteric organisms, and because it was previously used in various studies (16,17,(30)(31)(32)(33). We did not observe any improvement in survival after CLP by using a variety of antibiotic treatment protocols, including periprocedural, preprocedural, multiple-interval-dosing postprocedural, and even intracecal protocols.…”
Section: Figmentioning
confidence: 99%